2023
DOI: 10.1007/s12035-023-03736-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuritic Plaques — Gateways to Understanding Alzheimer’s Disease

Wangchen Tsering,
Stefan Prokop

Abstract: Extracellular deposits of amyloid-β (Aβ) in the form of plaques are one of the main pathological hallmarks of Alzheimer’s disease (AD). Over the years, many different Aβ plaque morphologies such as neuritic plaques, dense cored plaques, cotton wool plaques, coarse-grain plaques, and diffuse plaques have been described in AD postmortem brain tissues, but correlation of a given plaque type with AD progression or AD symptoms is not clear. Furthermore, the exact trigger causing the development of one Aβ plaque mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 129 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Previous studies showed that Aβ deposits may exert local toxicity that decreases with distance from the deposits [19,24]. Thus, we examined whether the losses of MAergic and Ach afferents were differentially affected as a function of distance from Aβ deposits.…”
Section: Spatial Relationship Between Degeneration Of Ach and 5-ht Af...mentioning
confidence: 95%
“…Previous studies showed that Aβ deposits may exert local toxicity that decreases with distance from the deposits [19,24]. Thus, we examined whether the losses of MAergic and Ach afferents were differentially affected as a function of distance from Aβ deposits.…”
Section: Spatial Relationship Between Degeneration Of Ach and 5-ht Af...mentioning
confidence: 95%